2021
DOI: 10.1186/s12864-021-07769-x
|View full text |Cite
|
Sign up to set email alerts
|

Chloroplast phylogenomics and divergence times of Lagerstroemia (Lythraceae)

Abstract: Background Crape myrtles, belonging to the genus Lagerstroemia L., have beautiful paniculate inflorescences and are cultivated as important ornamental tree species for landscaping and gardening. However, the phylogenetic relationships within Lagerstroemia have remained unresolved likely caused by limited sampling and the insufficient number of informative sites used in previous studies. Results In this study, we sequenced 20 Lagerstroemia chloropla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
20
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 47 publications
8
20
0
Order By: Relevance
“…In this study, the results of nucleotide diversity (Pi) assessment showed that the gene sequences of the LSC/SSC region were more variable than those in the IR region, which was consistent with the results found in other genera [13,41,[45][46][47]. The same conclusion has been reached in the study of Lagerstroemia and Adrinandra plants [48,49]. Through cp genome sequence variation analysis, we discovered five hypervariable regions in the LSC (rps12, trnW-CCA, and rps3) and SSC regions (rpl32 and ccsA).…”
Section: Discussionsupporting
confidence: 91%
“…In this study, the results of nucleotide diversity (Pi) assessment showed that the gene sequences of the LSC/SSC region were more variable than those in the IR region, which was consistent with the results found in other genera [13,41,[45][46][47]. The same conclusion has been reached in the study of Lagerstroemia and Adrinandra plants [48,49]. Through cp genome sequence variation analysis, we discovered five hypervariable regions in the LSC (rps12, trnW-CCA, and rps3) and SSC regions (rpl32 and ccsA).…”
Section: Discussionsupporting
confidence: 91%
“…The plastomic sequence is commonly described as a quadripartite structure with a large single-copy (LSC), a small single-copy (SSC), and a pair of inverted-repeat (IR) regions [ 36 ]. The angiosperm cp genomes are generally of moderate size, ranging from 120 to 160 kb [ 37 39 ]. With the rapid development of high throughput sequencing technology, the cp genome (chloroplast genome) is widely applied as a super-barcode, which could provide effective information for resolving phylogenetic relationships and identification of medicinal plants [ 40 42 ].…”
Section: Introductionmentioning
confidence: 99%
“…The chloroplast genomes in angiosperms usually have a circular structure, ranging from 115 to 165 kb in length, and typical quadripartite structures, which consist of two copies of a large inverted repeat (IR) region separated by a large single-copy (LSC) region and a small single-copy (SSC) region. Phylogenetic analyses based on whole chloroplast genome sequences have been widely used at different taxonomic levels [16][17][18][19][20][21][22][23][24] and have provided effective genetic markers to resolve complex evolutionary histories [25][26][27]. Parasitic plants have partially or entirely lost photosynthetic activity, and are assumed to relax normal constraints on evolution of the chloroplast genome (plastome).…”
Section: Introductionmentioning
confidence: 99%